USEFUL PROPERTIES OF NON-TRADITIONAL VEGETABLE CULTURE ARTICHOKE (CYNARA SCOLYMUS L) - Daughter of Madumarova Gulyora Cainjan (Journal of new century innovations, 2022)
Annotation. In addition to the plants that are constantly used throughout the human life, it is advisable to use fresh taste and flavor, in addition to other types of products that are naturally rich in nutrients that enter the body in small quantities, without interruption. One such product is the prickly Artichoke (Cynara Scolymus L), which belongs to the tetanus family. Artichoke (Cynara Scolymus L) has been unconventional for the Republic of Uzbekistan, but in many other countries it has been cultivated for several centuries as a favorite vegetable crop,medicinal crop and good fodder hashak crop.